2005
DOI: 10.1007/s00381-004-1099-8
|View full text |Cite
|
Sign up to set email alerts
|

Positive reaction for cysticercosis and multicentric anaplastic oligoastrocytoma

Abstract: Although some authors believe that chronic inflammatory changes following neurocysticercosis could induce the formation of brain tumors, this association may be a mere coincidence. In our case no clinical evidence of a prior infestation by Cysticercus was found. In fact, an exhaustive examination of the specimens did not reveal any areas of inflammatory reaction. We believe that the similarity of the glioma and cysticercosis antigens may be the cause of the positive reactions in the cystic fluid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…In our opinion, the possibility of a tumor developing from an unapparent parasitic lesion is invalidated by this finding. As stated by Salomão et al (10), the glioma and cysticercosis antigens are glycoproteins of a similar molecular weight, which may be the cause of the positive reaction for NCC in the cystic fluid.…”
Section: Discussionmentioning
confidence: 87%
“…In our opinion, the possibility of a tumor developing from an unapparent parasitic lesion is invalidated by this finding. As stated by Salomão et al (10), the glioma and cysticercosis antigens are glycoproteins of a similar molecular weight, which may be the cause of the positive reaction for NCC in the cystic fluid.…”
Section: Discussionmentioning
confidence: 87%
“…There is a wide range in age at presentation of multicentric gliomas, but the majority of patients are middle aged or older, and a few child cases have also been reported [2,7,8,10] . Some child cases with multicentric gliomas are induced by radiation, sometimes appearing after therapeutic irradiation.…”
Section: Discussionmentioning
confidence: 96%
“…Firstly, neoplastic transformation may develop in the wide area or whole of the brain, and somewhere become more susceptible to neoplastic growth. Secondly, the development of neoplastic proliferation in multiple sites, come from the same or different primitive cells, with various kinds of stimulation (biochemical, hormonal, viral, parasitic disease, etc) [1,2,7,8] . Most opinions tend to the common mechanism and a style of an active migratory process, either developing within the course of the disease (metachronous) or already being present at the time of fi rst tumor manifestation (synchronous) [9] .…”
Section: Discussionmentioning
confidence: 99%
“…A direct association between gliomas and NC has been reported [11] and might be more than a coincidence. An indirect association has been reported in studies that found positive reactions for cysticercosis in the cystic fluid of gliomas [12] raising the question of a cross reaction between the two pathologies. The association of NC and gliomas has been reported mainly in the endemic areas and raised the possibility of the parasitic disease acting as a risk factor for brain tumors.…”
Section: Discussionmentioning
confidence: 98%